Obturator with hollow bulb after hemimaxillectomy – A Case Report - Gunawan, Cynthia; Fransiscus Wihan Pradana; Endang Wahyuningtyas; Intan Ruspita (Indonesia Prosthodontic Association, 2024)
Hemimaxillectomy will create oro-nasal communication which can affect the function of swallowing, masticatory, speech, aesthetic and psychological. This case report describes a method of prosthodontic management of maxillary defects using an obturator prosthesis with a hollow bulb. A 15-year-old male patient was diagnosed with central giant cell granuloma, therefore hemimaxillectomy was performed by ENT doctors at RSUP Dr. Sardjito. He has a surgical obturator that was inserted by a prosthodontist immediately after the surgery. Three weeks after surgery, soft tissues were ready to be made an interim obturator. Seven months later, he came to RSGM Prof. Soedomo with a complaint the old obturator is difficult to adapt. Intraoral examination revealed a large palate defect in the right palate durum segment (Aramany's class II type maxillary defect) and half of the right maxilla is missing. A definitive obturator using metal combination acrylic with a hollow bulb was made to cover the maxillofacial defect and replaced missing teeth. That prosthesis can cover the defects of the maxilla so the patient can speak well, and the function of masticating and swallowing can be restored. Keywords: surgical obturator, definitive obturator, hollow bulb